Sharing Economy in the Neoliberal Era: A Critical Analysis through the Lens of Neoliberalism - Nidya Agustin (UNIDA Gontor, 2024)
This research aims to analyze the sharing economy from the perspective of neoliberalism using a qualitative research method. Conducting a literature review, the study seeks an in-depth understanding of the impact of the sharing economy phenomenon on individuals and society, in line with the principles of neoliberalism. Data is collected through the analysis of literature related to business models, regulations, and the social impact of the sharing economy. The findings highlight positive effects such as innovation, economic growth, and individual empowerment in alignment with neoliberal viewpoints. However, the study also identifies potential risks such as inequality, lack of consumer protection, and job uncertainty that require special attention in policy contexts. By integrating the perspective of neoliberalism, this research provides insights into the complexity of the sharing economy phenomenon and contributes to the literature's understanding of its impact. The implications of these findings are expected to form the basis for balanced policy-making, considering both free-market values and social justice in managing the sharing economy. Keywords: Free Market, Neoliberalism, Sharing Economy.